2017
DOI: 10.3899/jrheum.161161
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Baricitinib Through 128 Weeks in an Open-label, Longterm Extension Study in Patients with Rheumatoid Arthritis

Abstract: Objective.To assess the safety and efficacy of baricitinib in patients with rheumatoid arthritis (RA) up to 128 weeks in a phase IIb study (NCT01185353).Methods.After a 24-week blinded period, eligible patients entered an initial 52-week open-label extension (OLE); patients receiving 8 mg once daily (QD) continued with that dose and all others received 4 mg QD. Doses could be escalated to 8 mg QD at 28 or 32 weeks at investigator discretion when ≥ 6 tender and ≥ 6 swollen joints were present. Patients completi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 9 publications
(15 reference statements)
7
41
0
2
Order By: Relevance
“…In our extension study, all improvements in RA observed following the initial 12 weeks of active treatment were maintained (or further improved) during the next 52-week period (Figure 2). This pattern is similar to the results at weeks 24, 76, and 128 from a trial of baricitinib in a multinational population with active RA despite MTX therapy [11]. In addition, maintenance of efficacy with baricitinib up to 24 weeks has also been observed in patients with RA and an inadequate response to biologic DMARDs [8] or conventional synthetic DMARDs [7], and up to 52 weeks in DMARD-naïve patients [10].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In our extension study, all improvements in RA observed following the initial 12 weeks of active treatment were maintained (or further improved) during the next 52-week period (Figure 2). This pattern is similar to the results at weeks 24, 76, and 128 from a trial of baricitinib in a multinational population with active RA despite MTX therapy [11]. In addition, maintenance of efficacy with baricitinib up to 24 weeks has also been observed in patients with RA and an inadequate response to biologic DMARDs [8] or conventional synthetic DMARDs [7], and up to 52 weeks in DMARD-naïve patients [10].…”
Section: Discussionsupporting
confidence: 69%
“…The safety findings of this extension period were generally consistent with the initial 12-week treatment period [5], and with other international baricitinib studies with shortterm and long-term treatment [8,9,11]. Overall, baricitinib was well tolerated, and the nature of TEAEs and the incidence and nature of SAEs were similar between the 4 mg and 8 mg groups.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Adverse event rates were similar in the combined 4/8-mg baricitinib group and the placebo group. In the open-label extension of the study, clinical improvements observed with baricitinib were maintained through 128 weeks and safety signals were consistent with those seen in the first 12 weeks of treatment 10,11 .…”
Section: Rheumatologymentioning
confidence: 74%
“…Baricitinib is a JAK2 and JAK1 inhibitor, and multiple phase 3 clinical trials have shown its efficacy in RA. [68][69][70][71][72][73] Treatment-naïve patients with active RA showed significant responses to baricitinib both as monotherapy and in combination with methotrexate.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%